2007
DOI: 10.1375/twin.10.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Contributions to Pathological Gambling Symptoms in a 10-Year Follow-Up

Abstract: Problem (P) and pathological gambling (PG) symptoms wax and wane. Past symptoms are a risk for future symptoms even after controlling for familial influences. To address the genetic architecture of lifetime PG and current PG symptoms, we tested for common and unique genetic factors to lifetime PG symptoms at baseline and past year PG symptoms at 10-year follow-up. Diagnostic and Statistical Manual of Mental Disorders (3rd ed., Rev.; DSM-III-R; American Psychiatric Association, 1987) lifetime criteria of one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Finally, studies among twins found that PG was higher among co-twins of individuals with PG than co-twins of individuals without PG (Slutske et al 2001;Slutske et al 2009;Xian et al 2007). In sum, genetic influences might not determine the development of a specific expression of addiction; however, genetics does influence the risk of addiction in general.…”
Section: Neurobiological and Neurogenetic Factorsmentioning
confidence: 94%
“…Finally, studies among twins found that PG was higher among co-twins of individuals with PG than co-twins of individuals without PG (Slutske et al 2001;Slutske et al 2009;Xian et al 2007). In sum, genetic influences might not determine the development of a specific expression of addiction; however, genetics does influence the risk of addiction in general.…”
Section: Neurobiological and Neurogenetic Factorsmentioning
confidence: 94%
“…The results of this study suggest that PG is as heritable as alcohol dependence, and that genetic factors, rather than social modeling, predominantly explain the familial transmission of PG. In a 10-year follow-up of the Vietnam Era twin cohort, Xian et al (2007) found that the same genetic factors accounted for variation in liability for problem gambling at both the baseline and at the 10-year follow-up and that the estimates of heritability at the two time points were similar (baseline: 49%; follow-up: 58%). The results of this follow-up study suggest that the changes in the availability of gambling that occurred in the United States between 1992 and 2002 did not alter the underlying genetic architecture of the liability to problem gambling.…”
mentioning
confidence: 96%
“…The studies relating to the Vietnam Era Twin Registry contained problem and pathological gamblers with a diagnosis based on the DSM-III-R or DSM-IV classification system carried out by telephone interview [21][22][23][24][25]. For participants of the Australian Twin Registry Cohort, the NODS (National Opinion Research Center DSM-IV Screen for Gambling Problems) was applied to assess gambling-related problems, and is a tool that utilizes the DSM-IV criteria for pathological gambling [26].…”
Section: Methods Used In Twin Research Studies To Assess Problem and mentioning
confidence: 99%